Customer Loyalty Formation In E-Commerce: The Role Of Trust, Peer-To-Peer Communication, Purchase Decision, And Customer Satisfaction - Harimurti Wulandjani; Supriadi Thalib; Widarto Rachbini; Aryo Seno; Ahmad Fikri (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of trust and peer-to-peer communication on customer loyalty through purchase decision and customer satisfaction among Shopee users in DKI Jakarta. This study employed a quantitative approach using an explanatory research method. The sampling technique used purposive sampling with a total of 155 Shopee users in DKI Jakarta as respondents. Data analysis was conducted using Structural Equation Modeling–Partial Least Square (SEM-PLS) with the assistance of SmartPLS software. The results showed that trust had a positive and significant effect on purchase decision and customer satisfaction. Peer-to-peer communication was also proven to have a positive and significant effect on purchase decision and customer satisfaction. Furthermore, purchase decision had a positive and significant effect on customer satisfaction. Customer satisfaction was proven to have a positive and significant effect on customer loyalty among Shopee users in DKI Jakarta. The findings indicate that increasing consumer trust and positive communication among users can improve purchase decisions, customer satisfaction, and customer loyalty on e-commerce platforms. This study provides a theoretical contribution to the development of digital marketing management studies, particularly related to consumer behavior in the e-commerce industry. In addition, this study also provides practical implications for e-commerce companies in improving customer loyalty through strengthening trust and optimizing peer-to-peer communication Keywords: Trust, Peer to Peer Communication, Purchase Decision, Customer Satisfaction, Customer Loyalty, E-Commerce.